Peripheral Fragile X messenger ribonucleoprotein is required for the timely closure of a critical period for neuronal susceptibility in the ventral cochlear nucleus - Yu, Xiaoyan; Wang, Yuan (Frontiers in Cellular Neuroscience, 2023)
Alterations in neuronal plasticity and critical periods are common across neurodevelopmental diseases, including Fragile X syndrome (FXS), the leading single-gene cause of autism. Characterized with sensory dysfunction, FXS is the result of gene silencing of Fragile X messenger ribonucleoprotein 1 (FMR1) and loss of its product, Fragile X messenger ribonucleoprotein (FMRP). The mechanisms underlying altered critical period and sensory dysfunction in FXS are obscure. Here, we performed genetic and surgical deprivation of peripheral auditory inputs in wildtype and Fmr1 knockout (KO) mice across ages and investigated the effects of global FMRP loss on deafferentation-induced neuronal changes in the ventral cochlea nucleus (VCN) and auditory brainstem responses. The degree of neuronal cell loss during the critical period was unchanged in Fmr1 KO mice. However, the closure of the critical period was delayed. Importantly, this delay was temporally coincidental with reduced hearing sensitivity, implying an association with sensory inputs. Functional analyses further identified early-onset and long-lasting alterations in signal transmission from the spiral ganglion to the VCN, suggesting a peripheral site of FMRP action. Finally, we generated conditional Fmr1 KO (cKO) mice with selective deletion of FMRP in spiral ganglion but not VCN neurons. cKO mice recapitulated the delay in VCN critical period closure in Fmr1 KO mice, confirming an involvement of cochlear FMRP in shaping the temporal features of neuronal critical periods in the brain. Together, these results identify a novel peripheral mechanism of neurodevelopmental pathogenesis.